Pornografía de internet y comportamientos sexuales. Estudio en la Unidad Educativa Carlos Cisneros. Riobamba. Chimborazo. - Utreras Lozada, Alexis Mauricio (2022)
This research analyzes the relationship between Internet Pornography and Sexual Behaviors, pornography is a very controversial issue since there are many people who defend its existence and others who fight it. The objective of this research is to know if pornography found on the Internet can change sexual behavior. The beneficiaries of this research were a total of 67 students, divided into 43 males and 24 females of the first year of high school "A" and "B" of the Educational Unit "Carlos Cisneros", they were asked to fill out a questionnaire with 16 closed questions in which there were no right or wrong answers, the duration was 15 minutes. The method considered for the study is the quantitative approach; the non-experimental design and the type of study is cross-sectional, the technique used in the independent and dependent variables was an autarkic questionnaire. The results show that the majority of students have no problems in their sexual behavior and a minority that there are changes from watching pornographic videos. Therefore, it is concluded that a large part of students do not present bad sexual behaviors when exposed to videos with exaggerated sexual content.